(untitled) (Physical Education, Health and Social Sciences, 2026)
This study presents a comprehensive first-principles investigation of the structural, elastic, electronic, and optical properties of cubic CaCl2 and CaF2 compounds using density functional theory (DFT). The calculations were performed within the full-potential linearized augmented plane wave (FP-LAPW) framework. Structural optimization confirms that both compounds crystallize in a stable cubic phase, with equilibrium lattice parameters in good agreement with expected values. Elastic constant calculations satisfy the Born stability criteria, indicating mechanical stability of both materials, while comparative analysis reveals that CaF2 exhibits higher stiffness, bulk modulus, and ductility than CaCl2. Electronic band structure and density of states analyses demonstrate that both compounds are wide band gap insulators with indirect band gaps, where CaF2 shows a larger band gap due to stronger ionic bonding and higher electronegativity of fluorine. Optical properties, including dielectric function, absorption coefficient, reflectivity, and energy loss function, indicate negligible activity in the visible region and strong response in the ultraviolet range. CaF2 exhibits sharper and more intense optical peaks, suggesting superior performance in high-energy optical applications. Overall, the results highlight the potential of these materials, particularly CaF2 for use in ultraviolet optoelectronic devices and dielectric applications.